2015
DOI: 10.3892/ijo.2015.3167
|View full text |Cite
|
Sign up to set email alerts
|

Adherens junctions associated protein 1 serves as a predictor of recurrence of squamous cell carcinoma of the esophagus

Abstract: Esophageal squamous cell carcinoma (ESCC), the most common esophageal cancer in East Asia, is among the six cancers with the highest fatality rates worldwide. Unfortunately, multidisciplinary treatment strategies have not achieved satisfactory outcomes. Therefore, novel insights into the molecular biology of ESCC are required to improve treatment. The gene encoding the transmembrane adherens junctions-associated protein-1 (AJAP1) expressed by epithelial cells resides in chromosome 1p36, which is frequently los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 40 publications
2
27
0
Order By: Relevance
“…It has been shown that the expression of AJAP1 is dysregulated in various cancer types including glioma (Lin et al, 2012; McDonald et al, 2006), hepatocellular carcinoma (HCC) (Ezaka et al, 2015) and esophageal squamous cell carcinoma (ESCC) (Tanaka et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the expression of AJAP1 is dysregulated in various cancer types including glioma (Lin et al, 2012; McDonald et al, 2006), hepatocellular carcinoma (HCC) (Ezaka et al, 2015) and esophageal squamous cell carcinoma (ESCC) (Tanaka et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…The 'integrome' proposed by these authors represents integration of pathways, methylation status and gene expression in esophageal cancer. Other investigators identified epigenetic regulation of the transmembrane AJAP-1 and its association with recurrence of esophageal cancer [52].…”
Section: • Esophageal Cancermentioning
confidence: 99%
“…DNA methylation is a potential tumor marker for several cancers because of its heritable and stable characteristics [109]. DNA methylation at specific loci reflects the characteristic clinicopathological features [52]. Genome-wide analysis of DNA methylation has revealed that epigenetic regulation is not only a site-specific event but also spans long stretches of chromosome regions consisting of clusters of contiguous CpG islands [110,111].…”
Section: Components Of the Epigenome And Ewasmentioning
confidence: 99%
See 1 more Smart Citation
“…Esophageal squamous cell carcinoma (ESCC) is a dominant histological type of esophageal malignances (3,4). The poor prognosis and increasing incidence of ESCC highlight the need for improved detection, prediction, monitoring, and treatment methods (2,5).…”
Section: Introductionmentioning
confidence: 99%